The effect of tax administration applications (e-filing) on taxpayer complience with taxpayer understanding as an intervening variable (case study of wpop kpp pratama kudus) - Dannisa Zahroh; Rudi Yulianto, Ahmad (Jurnal Ekonomi, Manajemen dan Akuntansi (JEKMA), 2023)
The purpose of this study was to analyze the effect of e-filing on taxpayer compliance with taxpayer understanding as an intervening variable. The information for this study was obtained from the distribution of questionnaires addressed to taxpayers registered at KPP Pratama Kudus. The sampling technique used the random sampling method and a sample of 100 respondents was made. The analysis techniques used in this study are descriptive analysis and quantitative analysis (data quality test, classical assumption test, multiple regression analysis, hypothesis testing and model feasibility test) using SPSS software. The results of this study indicate that e-filing has a positive and significant effect on taxpayer understanding, taxpayer understanding has a positive and significant effect on taxpayer compliance, e-filing has a positive and significant effect on taxpayer compliance and e-filing has a positive and significant effect on taxpayer compliance through taxpayer understanding.Keywords: E-Filing, Taxpayer Compliance, Taxpayer Understanding